MYTHOPOETIC ASPECT OF M. Yu. LERMONTOV’S OEUVRE: THE MODERN STATE AND RESEARCH PROSPECTS (Revista Inclusiones, 2020)
The topicality of the problem under study is due; firstly, to the paraphrase of Lermontov’s ‘A Hero of Our Time’ in J. Littell’s ‘Les Bienveillantes’ (2006) and A. Brusnikin’s (a pen-name of B. Akunin) ‘A Hero of Another Time’ (2010) mythologizing the scene (Pyatigorsk) as well as the fates of Lermontov’s characters and the author himself; second, to a dramatic integration of folklore studies with ethnography, psychology and literature within the framework of the anagogic literature studies based upon K. G. Jung’s collective conscience archetypes. The article aims to decode the plot of the novel and the personality of the main character in a mythopoetic way to understand the nature of Pechorin’s fatalism. The key approach is the contextual analysis of the novel’s imagery enabling to reveal patterns and episodes indicative of the archaic elements of meaning relevant to the archetypes of Shadow, Child, Anima and Animus, Self (Personality) and Wise Man/Woman.